The invaluable experience: Martin Singer and Concordia's extraordinary path to open China's door to the world. Issue 4 (24th February 2020) - Lan, Kenneth
Abstract : Purpose: This writing examines the remarkable career of the founding East Asian scholar at Montreal's Concordia University. He was the individual who did more than merely a college professor after 37 years there. He had helped to shape a new course in Sino-Canadian relations. Design: This paper will look at an element of soft power engagement between Canada and China before Deng Xiaoping's Open Door Policy. It also examines Concordia's achievement in establishing a China foothold in the early-1980s. Findings: Canada has always been a pioneer in engaging Red China. Despite not having formal diplomatic ties until October 1970, Ottawa never abandoned its wish to seek a friendship with Beijing. Amidst the thawing China–Canada relations since 1970, Concordia University recruited a 25-year-old graduate student named Martin Singer to inaugurate its East Asian courses. Singer's auspicious academic career not only gave him to organize Canada's first and the largest student delegation to China but also enabled him to pioneer the first joint-postgraduate studies program between a Chinese and a Western postsecondary institution. He was also a key player in establishing a novel and unique relationship between the PRC and the Western world. Originality: This paper provides a glimpse into China's early experience in engaging the world as it left behind decades of communist isolation. It also highlights how serendipities allowed people and institutions to advance in the wake of this exciting period in modern Chinese history.